Living with Diabetes: Keeping Track of Your Blood Glucose - Linda B. Bobroff (EDIS)
Living with diabetes involves setting goals, adjusting your lifestyle to meet your treatment goals, evaluating your progress, and changing practices as needed. One key goal of diabetes management is to attain glycemic (blood glucose) control to reduce the risk of health complications. Healthy lifestyle practices, such as eating well, engaging in physical activity, and using medications as prescribed, contribute to glycemic control and to an overall healthy life. This 3-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, June 2013.